O canal de empréstimos bancários no Brasil: uma evidência microeconômica - Graminho, Flávia Mourão (2002)
The aim of this thesis is to investigate the existence and relevance of the bank-lending channel in Brazil. For that purpose we use balance-sheet data of Brazilian financial institutions, and adopt a methodology based in Kashyap and Stein (2000), who use twostage and panel estimations. We find that restrictive monetary policy – represented by interest rate increases – lower the sensibility of bank lending to the liquidity of its assets. In other words, increases in the interest rate lead to less binding bank liquidity restrictions. Therefore, the existence of a bank-lending channel for the transmission of monetary policy in Brazil is refused.